FEATURES OF CONCENTRATION ACID WHEY BY MEMRANE METHODS - Vladimir Georgievich Kulenko; Evgenya Alexandrovna Fialkova; Dmitriy Mikhaylovich Kostukov; Marina Sergeevna Zolotoreva; Ivan Alekseevich Evdokimov; Vladimir Borisovich Shcevchuk (Вестник Северо-Кавказского федерального университета, 2022)
In this article was investigated concentration of cottage cheese whey by baromembranes methods and determined the main regularities of concentration.